2002
DOI: 10.1073/pnas.012678999
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase expression targeted to gonadotropin-releasing hormone neurons inhibits luteinizing hormone pulses in transgenic rats

Abstract: Experiments in the GT1 gonadotropin-releasing hormone (GnRH) cell line have shown that the cAMP signaling pathway plays a central role in regulating the excitability of the cells. Lowering cAMP levels by expressing the constitutively active cAMP-specific phosphodiesterase PDE4D1 in GT1 cells inhibited spontaneous Ca 2؉ oscillations and intrinsic pulsatile GnRH secretion. To address the role of cAMP levels in endogenous GnRH neurons, we genetically targeted expression of PDE4D1 (P) to GnRH neurons in transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…This increases cell excitability and enhances firing of action potentials, leading to depolarization and elevation of [Ca 2ϩ ] i . The exact manner in which cAMP contributes to the episodic mode of GnRH secretion has yet to be determined, but its importance in the control of GnRH release is indicated by a recent study in rats expressing an active phosphodiesterase transgene in their GnRH neurons (34). However, it is likely that cAMP is essential but not alone sufficient for the generation of pulsatile GnRH release.…”
Section: Discussionmentioning
confidence: 99%
“…This increases cell excitability and enhances firing of action potentials, leading to depolarization and elevation of [Ca 2ϩ ] i . The exact manner in which cAMP contributes to the episodic mode of GnRH secretion has yet to be determined, but its importance in the control of GnRH release is indicated by a recent study in rats expressing an active phosphodiesterase transgene in their GnRH neurons (34). However, it is likely that cAMP is essential but not alone sufficient for the generation of pulsatile GnRH release.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, decreasing cAMP levels by the expression of a constitutively active PDE4D1 inhibited forskolin-induced cAMP production and GnRH secretion [37]. Furthermore, decreasing cAMP levels in vivo by the overexpression of PDE4D1 targeted to GnRH neurons not only reduced the release of GnRH but also decreased the fertility rate in rats [38, 39]. However, despite the importance of the AC/cAMP signaling pathway as a central modulator of GnRH secretion, very little was known about the AC family in GnRH neurons.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that the frequency of LH pulses in OVX GPR-4 rat was significantly decreased relative to WT littermate controls [18]. We extended these findings to determine if pulsatile FSH secretion was also affected and whether there was concordance between LH and FSH pulses.…”
Section: Resultsmentioning
confidence: 50%
“…Expression of PDE4D1 was specifically targeted to GnRH neurons in the GPR-4 rat transgenic line using the promoter/enhancer regions of the rat GnRH gene [18]. The transgene consisted of 3 kb of the promoter/enhancer region of the rat GnRH gene inserted upstream of the B intron of the rabbit β-globin gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation